PSIKOLOGIS PENGARANG DALAM LIRIK LAGU ALBUM “DOSA, KOTA, DAN KENANGAN” KARYA SILAMPUKAU - Malendra Pradana, Tio; Pramujiono, Agung (Universitas PGRI Adi Buana Surabaya, 2019)
This research is motivated by the fact that each of the creative process in the creation of aliterary work is a personal reflection author. The personal things, including psychologicalfactors within the author closely related to the events that the author never experienced in thepast. In addition to the author's personal experience, culture and literacy authors also take partin determining the quality of a literary work. In this study, the researchers raised concernsabout the psychology of the author of the lyrics of the song Silampukau. The purpose of thisstudy was to describe how the association psychology author of the lyrics of the song album